A long-lasting anti-icing coating containing polysiloxane and a method of making the same

By constructing a cross-linkable core-shell structure on the silica surface and introducing fluorine chains, the problem of large polarity difference between fluorine compounds and organosilicon coatings and easy detachment was solved. This achieved a balance between the long-term performance and mechanical strength of the anti-icing coating, and improved the coating's wear resistance and low-temperature impact resistance.

CN121064724BActive Publication Date: 2026-05-15SUZHOU LANWOQI NANOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511350482.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-22
Publication Date
2026-05-15
Estimated Expiration
2045-09-22

AI Technical Summary

Technical Problem

Fluorine compounds and organosilicon coatings have a large difference in polarity, making it impossible to form a stable structure and causing them to easily peel off, resulting in a rapid decline in anti-icing performance.

Method used

By constructing a crosslinkable core-shell structure on the surface of silica and introducing fluorine chains, a polysiloxane-containing coating is formed. The hydrophilic amide groups and crosslinking anchoring sites are synergistically introduced using an organosilicon intermediate layer to enhance the bonding strength of the core-shell interface. Furthermore, the water distribution of the surface hydrophobic fluorine chain array and the inner amide groups is regulated through layered structural modification, forming molecular-level connections and surface energy gradients.

Benefits of technology

It achieves a balance between the long-term performance and mechanical strength of the anti-icing coating, improves the coating's wear resistance and low-temperature impact resistance, and ensures stable anti-icing performance in complex service environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of coating, in particular to a long-acting anti-icing coating containing polysiloxane and a preparation method thereof. The coating uses hydroxyl polysiloxane, tetraethyl orthosilicate, fluorine chain modified cross-linkable core-shell silica and the like as main raw materials, realizes efficient anchoring of fluorine chain and molecular level combination of the organic silicon matrix by constructing a hierarchical core-shell structure with high binding energy. At the same time, a proper amount of dimethyl silicone oil (150-250 mPa·s) is introduced to synergistically control the viscoelasticity and stress dispersion of the matrix, thereby improving the long-acting anti-icing performance. The strategy of cross-linking first and then fluorination is adopted, so that the hydrophobic fluorine chain is aggregated on the surface of the nanoparticles, and a dense cross-linked network is formed in the inside, thereby effectively improving the mechanical strength, wear resistance and low-temperature impact resistance of the coating. The prepared coating not only significantly reduces the ice adhesion, but also has excellent durability and multiple cycle use performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating technology, and in particular to a long-lasting anti-icing coating containing polysiloxane and its preparation method. Background Technology

[0002] Anti-icing coating technology has received widespread attention in recent years as an important means to solve the problem of equipment icing in low-temperature environments. Traditional anti-icing strategies are mainly divided into two categories: active heating and passive protection. Although active heating is effective, it consumes a lot of energy and the equipment is complex, making it difficult to apply in large areas or remote regions. Therefore, passive protective anti-icing coatings have become a research hotspot.

[0003] The core principle of passive anti-icing coatings lies in reducing the adhesion strength between the ice layer and the substrate surface, making it easier for ice to detach under external forces. Early research mainly focused on hydrophobic coatings, inhibiting water droplet wetting and icing by increasing surface hydrophobicity. However, purely hydrophobic strategies have significant limitations: in extremely low temperature environments, even hydrophobic surfaces cannot completely prevent icing; at the same time, hydrophobic coatings often have low mechanical strength and are prone to wear and failure in practical use.

[0004] To overcome these problems, researchers have begun to focus on anti-icing surfaces with special micro / nano structures. These surfaces enhance mechanical stability while maintaining hydrophobicity by constructing hierarchical microstructures. Fluorine-modified materials, due to their ultra-low surface energy and chemical inertness, have become an ideal choice. The extremely high CF bond energy of fluorine compounds endows the materials with excellent chemical stability and hydrophobic / oleophobic properties, enabling them to maintain stable anti-icing performance even in harsh environments.

[0005] Silicone coatings are widely used as protective coating substrates due to their excellent weather resistance, flexibility, and low surface tension. Introducing fluorine into silicone coatings promises to yield anti-icing coatings with superior overall performance. However, significant technical obstacles have been encountered in practical applications: the strong hydrophobicity of fluorine compounds and the moderate polarity of silicone create significant compatibility issues, making it difficult for fluorine compounds to be uniformly dispersed in the coating; more seriously, due to insufficient interfacial adhesion, fluorine compounds easily detach from the silicone matrix, leading to a rapid decline in coating performance. Summary of the Invention

[0006] In view of this, the purpose of this invention is to provide a long-lasting anti-icing coating containing polysiloxane and its preparation method, so as to solve the problem that the large polarity difference between fluorinated compounds and organosilicon coatings makes it impossible to form a stable structure and easy to fall off.

[0007] To achieve the above objectives, the present invention provides a long-lasting anti-icing coating containing polysiloxane, which is prepared by weight from the following raw materials: 30-50 parts hydroxyl polysiloxane, 5-10 parts dimethyl silicone oil, 6-14 parts tetraethyl orthosilicate, 10-20 parts fluorine-modified crosslinkable core-shell silica, 0.5-1 part dibutyltin dilaurate, 100-200 parts tetrahydrofuran, and 30-70 parts deionized water.

[0008] Preferably, the viscosity of the hydroxyl polysiloxane is 10000-50000 mPa·s.

[0009] Preferably, the viscosity of the dimethyl silicone oil is 150-250 mPa·s.

[0010] Preferably, the preparation steps of the fluorine chain modified crosslinkable core-shell silica are as follows:

[0011] S1: Vinyltrimethoxysilane graft-modified nano-silica yields alkenylated silica;

[0012] S2: First, acrylamide, vinyltrimethoxysilane and N,N'-methylenebisacrylamide are crosslinked and polymerized on the surface of alkenylated silica. After crosslinking and polymerization, hexafluorobutyl acrylate is further grafted and polymerized to obtain fluorine-chain modified crosslinkable core-shell silica.

[0013] Preferably, the average particle size of the nano-silica in step S1 is 20-100 nm.

[0014] Preferably, in step S1, the weight ratio of vinyltrimethoxysilane to nano-silica is 0.3-0.7:8-12.

[0015] Preferably, in step S2, the weight ratio of acrylamide, vinyltrimethoxysilane, N,N'-methylenebisacrylamide, alkenylated silica and hexafluorobutyl acrylate is 5-15:3-7:0.5-1.5:8-12:10-20.

[0016] Furthermore, the present invention also provides a method for preparing a long-lasting anti-icing coating containing polysiloxane, comprising the following steps:

[0017] (1) Add hydroxyl polysiloxane, dimethyl silicone oil and tetraethyl orthosilicate to a mixed solvent of tetrahydrofuran and deionized water, stir at room temperature for 20-40 min, then add fluorine chain modified crosslinkable core-shell silica and dibutyltin dilaurate, continue stirring for 15-25 min, then raise the temperature to 45-55℃, continue stirring for 40-60 min to obtain a prepolymer dispersion;

[0018] (2) The aluminum alloy substrate is ultrasonically cleaned, dried with nitrogen, and then plasma treated to obtain a pretreated substrate.

[0019] (3) Spray the prepolymer dispersion onto the surface of the pretreated substrate, let it stand for 3-8 minutes to level, cure, and then let it cool naturally to room temperature to obtain a long-lasting anti-icing coating containing polysiloxane.

[0020] Preferably, in step (2), the plasma treatment is performed using an oxygen plasma treatment machine with a power of 80-120 W and a time of 1-3 min.

[0021] Preferably, the spraying pressure in step (3) is 0.2-0.4 MPa and the nozzle distance is 10-20 cm.

[0022] Preferably, in step (3), the curing process involves pre-curing at 60-70℃ for 15-25 minutes, followed by heating to 115-125℃ and continuing curing for 1-3 hours.

[0023] Preferably, the thickness of the long-lasting anti-icing coating containing polysiloxane in step (3) is 15-25 μm.

[0024] The beneficial effects of this invention are:

[0025] This invention achieves a synergistically optimized polysiloxane anti-icing coating formulation by constructing a crosslinkable core-shell structure on the silica surface and introducing fluorine chains. This invention overcomes the application bottlenecks of traditional fluorinated silica materials in organosilicon coatings, such as poor dispersibility, low compatibility, and fluorine chain shedding, endowing the coating with excellent long-lasting anti-icing performance and durability. Firstly, by synergistically introducing hydrophilic amide groups and crosslinking anchoring sites through an organosilicon intermediate layer, molecular-level linkages are formed between the core nanoparticles and the outer organosilicon matrix, greatly enhancing the bonding strength of the core-shell interface and effectively preventing interfacial separation and performance degradation caused by freeze-thaw cycles, friction, or impact.

[0026] Furthermore, the layered modified structure endows the coating surface with a highly ordered array of hydrophobic fluorine chains, which can significantly reduce the binding force between ice crystals and the surface. On the other hand, the inner amide groups achieve molecular-level water film densification by regulating the distribution of interfacial water, thereby precisely controlling the surface energy gradient of the micro / nano structure. This multi-component synergistic effect not only achieves a balance between anti-icing effect and mechanical strength, but also effectively improves the coating's wear resistance and low-temperature impact resistance. Under repeated freezing and friction wear conditions, the coating can still maintain the integrity of the surface microstructure, and the ice adhesion performance does not show significant attenuation, indicating that this structural system can meet the application requirements of complex service environments.

[0027] Furthermore, the synthesis process design of this invention emphasizes the spatial control of the crosslinking sequence and fluorine chain distribution, effectively avoiding structural phase separation and degradation of the material's mechanical strength. By employing a strategy of crosslinking before fluorination, the hydrophobic fluorine chains are primarily distributed on the outermost surface of the nanoparticles, forming a dense and highly stable crosslinked network within. This not only enhances the self-healing ability of the coating surface but also promotes stress dispersion and energy dissipation, significantly improving the overall long-term service life of the material.

[0028] In summary, this invention achieves molecular-level synergistic interface regulation, cross-scale structural stability, and multifunctional performance coupling. While improving anti-icing performance, it also significantly enhances the mechanical durability and low-temperature adaptability of the coating, providing a novel solution for the design and application of reliable and long-lasting anti-icing materials in extreme environments. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0030] Example 1

[0031] (1) Under a nitrogen atmosphere, 8g of nano-silica (average particle size 50nm) was added to a mixed solvent of 20g deionized water and 50g anhydrous ethanol, ultrasonically treated for 8min, then 0.3g of vinyltrimethoxysilane was added, the temperature was raised to 50℃, the reaction was stirred for 5h, the temperature was lowered to room temperature, centrifuged, washed 3 times with anhydrous ethanol, and vacuum dried to obtain alkenylated silica;

[0032] (2) Under a nitrogen atmosphere, 8g of alkenylated silica, 5g of acrylamide, 3g of vinyltrimethoxysilane and 0.5g of N,N'-methylenebisacrylamide were added to 80g of toluene and sonicated for 20min. Then 0.1g of azobisisobutyronitrile was added and stirred at room temperature for 20min. The temperature was then raised to 75℃ and stirred for 20h. The temperature was then lowered to room temperature, 10g of hexafluorobutyl acrylate and 0.1g of azobisisobutyronitrile were added and stirred at room temperature for 20min. The temperature was then raised to 75℃ and stirred for 10h. The temperature was then lowered to room temperature, centrifuged, washed three times with toluene, and vacuum dried to obtain fluorine-chain modified crosslinkable core-shell silica.

[0033] (3) Add 30g of hydroxyl polysiloxane (viscosity 20000mPa·s), 5g of dimethyl silicone oil (viscosity 200mPa·s) and 6g of tetraethyl orthosilicate to a mixed solvent of 100g of tetrahydrofuran and 30g of deionized water, stir at room temperature for 20min, then add 10g of fluorine chain modified crosslinkable core-shell silica and 0.5g of dibutyltin dilaurate, continue stirring for 15min, then heat to 45℃ and continue stirring for 40min to obtain a prepolymer dispersion;

[0034] (4) The aluminum alloy substrate (100 mm × 100 mm × 1 mm) was ultrasonically cleaned with acetone and ethanol for 8 min in sequence, dried with nitrogen, and then the surface of the substrate was treated with oxygen plasma treatment machine (power 80W) for 1 min to obtain the pretreated substrate.

[0035] (5) Spray the prepolymer dispersion onto the surface of the pretreated substrate with a spraying pressure of 0.2 MPa and a nozzle distance of 10 cm. Let it stand for 3 min to level, then place it in a 60℃ oven for 15 min to pre-cur. Then raise the temperature to 115℃ and continue curing for 1 h. After curing, let it cool naturally to room temperature to obtain a long-lasting anti-icing coating containing polysiloxane with a dry film thickness of 16.1 μm.

[0036] Example 2

[0037] (1) Under a nitrogen atmosphere, 10g of nano-silica (average particle size 50nm) was added to a mixed solvent of 30g deionized water and 70g anhydrous ethanol, ultrasonically treated for 10min, and then 0.5g of vinyltrimethoxysilane was added. The temperature was raised to 55℃, stirred for 6h, cooled to room temperature, centrifuged, washed 3 times with anhydrous ethanol, and vacuum dried to obtain alkenylated silica.

[0038] (2) Under a nitrogen atmosphere, 10g of alkenylated silica, 10g of acrylamide, 5g of vinyltrimethoxysilane and 1g of N,N'-methylenebisacrylamide were added to 100g of toluene and sonicated for 30min. Then 0.16g of azobisisobutyronitrile was added and stirred at room temperature for 30min. The temperature was then raised to 80℃ and stirred for 24h. The temperature was then lowered to room temperature, 15g of hexafluorobutyl acrylate and 0.15g of azobisisobutyronitrile were added and stirred at room temperature for 30min. The temperature was then raised to 80℃ and stirred for 12h. The temperature was then lowered to room temperature, centrifuged, washed three times with toluene, and vacuum dried to obtain fluorine-chain modified crosslinkable core-shell silica.

[0039] (3) Add 40g of hydroxyl polysiloxane (viscosity 20000mPa·s), 7.5g of dimethyl silicone oil (viscosity 200mPa·s) and 10g of tetraethyl orthosilicate to a mixed solvent of 150g of tetrahydrofuran and 50g of deionized water, stir at room temperature for 30min, then add 15g of fluorine chain modified crosslinkable core-shell silica and 0.8g of dibutyltin dilaurate, continue stirring for 20min, then raise the temperature to 50℃ and continue stirring for 50min to obtain a prepolymer dispersion;

[0040] (4) The aluminum alloy substrate (100 mm × 100 mm × 1 mm) was ultrasonically cleaned with acetone and ethanol for 10 min in sequence, dried with nitrogen, and then treated with oxygen plasma treatment machine (power 100 W) for 2 min to obtain pretreated substrate.

[0041] (5) The prepolymer dispersion was sprayed onto the surface of the pretreated substrate at a spraying pressure of 0.3 MPa and a nozzle distance of 15 cm. After standing and leveling for 5 min, it was placed in a 65°C oven for pre-curing for 20 min. The temperature was then raised to 120°C and cured for 1.5 h. After curing, it was naturally cooled to room temperature to obtain a long-lasting anti-icing coating containing polysiloxane with a dry film thickness of 20.4 μm.

[0042] Example 3

[0043] (1) Under a nitrogen atmosphere, 12g of nano-silica (average particle size 50nm) was added to a mixed solvent of 40g deionized water and 90g anhydrous ethanol, ultrasonically treated for 12min, and then 0.7g of vinyltrimethoxysilane was added. The temperature was raised to 60℃, the reaction was stirred for 7h, cooled to room temperature, centrifuged, washed 3 times with anhydrous ethanol, and vacuum dried to obtain alkenylated silica.

[0044] (2) Under a nitrogen atmosphere, 12g of alkenylated silica, 15g of acrylamide, 7g of vinyltrimethoxysilane and 1.5g of N,N'-methylenebisacrylamide were added to 120g of toluene and sonicated for 40min. Then 0.2g of azobisisobutyronitrile was added and stirred at room temperature for 40min. The temperature was then raised to 85℃ and stirred for 28h. The temperature was then lowered to room temperature, 20g of hexafluorobutyl acrylate and 0.2g of azobisisobutyronitrile were added and stirred at room temperature for 40min. The temperature was then raised to 85℃ and stirred for 14h. The temperature was then lowered to room temperature, centrifuged, washed three times with toluene, and vacuum dried to obtain fluorine-chain modified crosslinkable core-shell silica.

[0045] (3) Add 50g of hydroxyl polysiloxane (viscosity 20000mPa·s), 10g of dimethyl silicone oil (viscosity 200mPa·s) and 14g of tetraethyl orthosilicate to a mixed solvent of 200g of tetrahydrofuran and 70g of deionized water, stir at room temperature for 40min, then add 20g of fluorine chain modified crosslinkable core-shell silica and 1g of dibutyltin dilaurate, continue stirring for 25min, then raise the temperature to 55℃ and continue stirring for 60min to obtain a prepolymer dispersion;

[0046] (4) The aluminum alloy substrate (100 mm × 100 mm × 1 mm) was ultrasonically cleaned with acetone and ethanol for 12 min in sequence, dried with nitrogen, and then treated with oxygen plasma treatment machine (power 120 W) for 3 min to obtain the pretreated substrate.

[0047] (5) The prepolymer dispersion was sprayed onto the surface of the pretreated substrate at a spraying pressure of 0.4 MPa and a nozzle distance of 20 cm. After standing and leveling for 8 min, it was placed in a 70°C oven for pre-curing for 25 min. The temperature was then raised to 125°C and cured for 3 h. After curing, it was naturally cooled to room temperature to obtain a long-lasting anti-icing coating containing polysiloxane with a dry film thickness of 24.2 μm.

[0048] Comparative Example 1:

[0049] The difference between Comparative Example 1 and Example 2 is that vinyltrimethoxysilane in step (2) is replaced with acrylamide;

[0050] The specific steps are as follows:

[0051] (1) Under a nitrogen atmosphere, 10g of nano-silica (average particle size 50nm) was added to a mixed solvent of 30g deionized water and 70g anhydrous ethanol, ultrasonically treated for 10min, and then 0.5g of vinyltrimethoxysilane was added. The temperature was raised to 55℃, stirred for 6h, cooled to room temperature, centrifuged, washed 3 times with anhydrous ethanol, and vacuum dried to obtain alkenylated silica.

[0052] (2) Under a nitrogen atmosphere, 10g of alkenylated silica, 15g of acrylamide and 1g of N,N'-methylenebisacrylamide were added to 100g of toluene and sonicated for 30min. Then 0.16g of azobisisobutyronitrile was added and stirred at room temperature for 30min. The temperature was then raised to 80℃ and stirred for 24h. The temperature was then lowered to room temperature, 15g of hexafluorobutyl acrylate and 0.15g of azobisisobutyronitrile were added and stirred at room temperature for 30min. The temperature was then raised to 80℃ and stirred for 12h. The temperature was then lowered to room temperature, centrifuged, washed three times with toluene, and vacuum dried to obtain fluorine-chain modified crosslinkable core-shell silica.

[0053] (3) Add 40g of hydroxyl polysiloxane (viscosity 20000mPa·s), 7.5g of dimethyl silicone oil (viscosity 200mPa·s) and 10g of tetraethyl orthosilicate to a mixed solvent of 150g of tetrahydrofuran and 50g of deionized water, stir at room temperature for 30min, then add 15g of fluorine chain modified crosslinkable core-shell silica and 0.8g of dibutyltin dilaurate, continue stirring for 20min, then raise the temperature to 50℃ and continue stirring for 50min to obtain a prepolymer dispersion;

[0054] (4) The aluminum alloy substrate (100 mm × 100 mm × 1 mm) was ultrasonically cleaned with acetone and ethanol for 10 min in sequence, dried with nitrogen, and then treated with oxygen plasma treatment machine (power 100 W) for 2 min to obtain pretreated substrate.

[0055] (5) Spray the prepolymer dispersion onto the surface of the pretreated substrate with a spraying pressure of 0.3 MPa and a nozzle distance of 15 cm. Let it stand for 5 min to level, then place it in a 65°C oven for 20 min to pre-cur. Then raise the temperature to 120°C and continue curing for 1.5 h. After curing, let it cool naturally to room temperature to obtain a coating with a dry film thickness of 19.3 μm.

[0056] Comparative Example 2:

[0057] The difference between Comparative Example 2 and Example 2 is that the acrylamide in step (2) is replaced with vinyltrimethoxysilane;

[0058] The specific steps are as follows:

[0059] (1) Under a nitrogen atmosphere, 10g of nano-silica (average particle size 50nm) was added to a mixed solvent of 30g deionized water and 70g anhydrous ethanol, ultrasonically treated for 10min, and then 0.5g of vinyltrimethoxysilane was added. The temperature was raised to 55℃, stirred for 6h, cooled to room temperature, centrifuged, washed 3 times with anhydrous ethanol, and vacuum dried to obtain alkenylated silica.

[0060] (2) Under a nitrogen atmosphere, 10g of alkenylated silica, 15g of vinyltrimethoxysilane and 1g of N,N'-methylenebisacrylamide were added to 100g of toluene and sonicated for 30min. Then 0.16g of azobisisobutyronitrile was added and stirred at room temperature for 30min. The temperature was then raised to 80℃ and stirred for 24h. The temperature was then lowered to room temperature, 15g of hexafluorobutyl acrylate and 0.15g of azobisisobutyronitrile were added and stirred at room temperature for 30min. The temperature was then raised to 80℃ and stirred for 12h. The temperature was then lowered to room temperature, centrifuged, washed three times with toluene, and vacuum dried to obtain fluorine-chain modified crosslinkable core-shell silica.

[0061] (3) Add 40g of hydroxyl polysiloxane (viscosity 20000mPa·s), 7.5g of dimethyl silicone oil (viscosity 200mPa·s) and 10g of tetraethyl orthosilicate to a mixed solvent of 150g of tetrahydrofuran and 50g of deionized water, stir at room temperature for 30min, then add 15g of fluorine chain modified crosslinkable core-shell silica and 0.8g of dibutyltin dilaurate, continue stirring for 20min, then raise the temperature to 50℃ and continue stirring for 50min to obtain a prepolymer dispersion;

[0062] (4) The aluminum alloy substrate (100 mm × 100 mm × 1 mm) was ultrasonically cleaned with acetone and ethanol for 10 min in sequence, dried with nitrogen, and then treated with oxygen plasma treatment machine (power 100 W) for 2 min to obtain pretreated substrate.

[0063] (5) Spray the prepolymer dispersion onto the surface of the pretreated substrate with a spraying pressure of 0.3 MPa and a nozzle distance of 15 cm. Let it stand and level for 5 min, then place it in a 65°C oven for 20 min to pre-cur it. Then raise the temperature to 120°C and continue curing for 1.5 h. After curing, let it cool naturally to room temperature to obtain the coating.

[0064] Comparative Example 3:

[0065] The difference between Comparative Example 3 and Example 2 is that in step (2), 15g of hexafluorobutyl acrylate and 0.15g of azobisisobutyronitrile are added first, and after the reaction, 10g of alkenylated silica, 10g of acrylamide, 5g of vinyltrimethoxysilane and 1g of N,N'-methylenebisacrylamide are added.

[0066] The specific steps are as follows:

[0067] (1) Under a nitrogen atmosphere, 10g of nano-silica (average particle size 50nm) was added to a mixed solvent of 30g deionized water and 70g anhydrous ethanol, ultrasonically treated for 10min, and then 0.5g of vinyltrimethoxysilane was added. The temperature was raised to 55℃, stirred for 6h, cooled to room temperature, centrifuged, washed 3 times with anhydrous ethanol, and vacuum dried to obtain alkenylated silica.

[0068] (2) Under a nitrogen atmosphere, 10g of alkenylated silica and 15g of hexafluorobutyl acrylate were added to 100g of toluene and sonicated for 30min. Then, 0.15g of azobisisobutyronitrile was added and stirred at room temperature for 30min. The temperature was raised to 80℃ and stirred for 12h. The temperature was lowered to room temperature, and 10g of acrylamide, 5g of vinyltrimethoxysilane and 1g of N,N'-methylenebisacrylamide were added. The temperature was raised to 80℃ and stirred for 24h. The temperature was lowered to room temperature, centrifuged, washed three times with toluene, and vacuum dried to obtain core-shell silica.

[0069] (3) Add 40g of hydroxyl polysiloxane (viscosity 20000mPa·s), 7.5g of dimethyl silicone oil (viscosity 200mPa·s) and 10g of tetraethyl orthosilicate to a mixed solvent of 150g of tetrahydrofuran and 50g of deionized water, stir at room temperature for 30min, then add 15g of core-shell silica and 0.8g of dibutyltin dilaurate, continue stirring for 20min, then heat to 50℃ and continue stirring for 50min to obtain a prepolymer dispersion;

[0070] (4) The aluminum alloy substrate (100 mm × 100 mm × 1 mm) was ultrasonically cleaned with acetone and ethanol for 10 min in sequence, dried with nitrogen, and then treated with oxygen plasma treatment machine (power 100 W) for 2 min to obtain pretreated substrate.

[0071] (5) Spray the prepolymer dispersion onto the surface of the pretreated substrate with a spraying pressure of 0.3 MPa and a nozzle distance of 15 cm. Let it stand for 5 min to level, then place it in a 65°C oven for 20 min to pre-cur. Then raise the temperature to 120°C and continue curing for 1.5 h. After curing, let it cool naturally to room temperature to obtain a coating with a dry film thickness of 19.8 μm.

[0072] Comparative Example 4:

[0073] The difference between Comparative Example 4 and Example 2 is that only hexafluorobutyl acrylate is used to polymerize on the surface of alkenylated silica in step (2);

[0074] The specific steps are as follows:

[0075] (1) Under a nitrogen atmosphere, 10g of nano-silica (average particle size 50nm) was added to a mixed solvent of 30g deionized water and 70g anhydrous ethanol, ultrasonically treated for 10min, and then 0.5g of vinyltrimethoxysilane was added. The temperature was raised to 55℃, stirred for 6h, cooled to room temperature, centrifuged, washed 3 times with anhydrous ethanol, and vacuum dried to obtain alkenylated silica.

[0076] (2) Under a nitrogen atmosphere, 10g of alkenylated silica and 15g of hexafluorobutyl acrylate were added to 100g of toluene, ultrasonically treated for 30min, and then 0.15g of azobisisobutyronitrile was added. The mixture was stirred at room temperature for 30min, heated to 80℃, stirred and polymerized for 12h, cooled to room temperature, centrifuged, washed 3 times with toluene, and vacuum dried to obtain core-shell silica.

[0077] (3) Add 40g of hydroxyl polysiloxane (viscosity 20000mPa·s), 7.5g of dimethyl silicone oil (viscosity 200mPa·s) and 10g of tetraethyl orthosilicate to a mixed solvent of 150g of tetrahydrofuran and 50g of deionized water, stir at room temperature for 30min, then add 15g of core-shell silica and 0.8g of dibutyltin dilaurate, continue stirring for 20min, then heat to 50℃ and continue stirring for 50min to obtain a prepolymer dispersion;

[0078] (4) The aluminum alloy substrate (100 mm × 100 mm × 1 mm) was ultrasonically cleaned with acetone and ethanol for 10 min in sequence, dried with nitrogen, and then treated with oxygen plasma treatment machine (power 100 W) for 2 min to obtain pretreated substrate.

[0079] (5) Spray the prepolymer dispersion onto the surface of the pretreated substrate with a spraying pressure of 0.3 MPa and a nozzle distance of 15 cm. Let it stand for 5 min to level, then place it in a 65°C oven for 20 min to pre-cur. Then raise the temperature to 120°C and continue curing for 1.5 h. After curing, let it cool naturally to room temperature to obtain a coating with a dry film thickness of 20.1 μm.

[0080] Performance testing:

[0081] Ice adhesion test: Each sample was placed in an environmental chamber at -20℃±0.5℃ for 24 hours. Ultrapure water was vertically sprayed using an atomizing spray gun (nozzle diameter 0.3mm) at a spray rate of 2mL / cm. 2 The sample was subjected to a centrifugal rotation (radius 200 mm) until a uniform ice layer of 0.25 ± 0.03 mm was formed on the surface. The sample was fixed on a centrifugal turntable (radius 200 mm) at -20℃ and run at an initial speed of 200 rpm for 60 seconds. The speed was increased by 50 rpm each time until the ice layer was completely peeled off. The critical speed at which the ice layer was completely peeled off was recorded, which represents the ice adhesion. The ice adhesion test was repeated 10 times, and the critical speed of the 10th test was recorded. The results are shown in Table 1.

[0082] Wear resistance and durability test: The coating was subjected to a 5000-rotation wear test using a Taber wear tester (CS-10 grinding wheel, 500g load). After wear, the ice adhesion test was performed, and the critical speed at which the ice layer was completely peeled off was recorded. The results are shown in Table 1.

[0083] Low-temperature impact resistance test: The sample was pretreated in a low-temperature chamber at -40℃±1℃ for 4 hours. Using a QCJ impact tester, a 1000g±1g hammer was lifted to a height of 50cm and dropped freely onto the center of the coating. The impact area was immediately examined with a 40x magnifying glass and graded according to the standard: Grade 0: No cracking or peeling; Grade 1: Fine cracks (<1mm); Grade 2: Network cracks (1-3mm); Grade 3: Peeling area >5mm. 2 The results are shown in Table 1.

[0084]

[0085] Data Analysis:

[0086] Performance data from Examples 1-3 show that the coating exhibits optimized synergy in terms of ice adhesion, durability, and low-temperature impact resistance. The ice adhesion strength did not significantly increase after multiple freeze-thaw cycles, suggesting that the surface micro / nano structure may be maintained through a dual physical-chemical crosslinking of the organosilicon segments and the core-shell interlayer. The consistently low-temperature impact resistance rating of ≤1 reflects that stress transfer between the silica core and the organosilicon coating is uniformly dispersed through the crosslinking network, preventing crack propagation caused by localized stress concentration. This synergistic effect is presumably due to the ordered regulation of water molecules achieved by the hydrophilic groups of acrylamide, the siloxane crosslinking sites provided by vinyltrimethoxysilane, and the synergistic optimization of interfacial compatibility by the core-shell layered structure.

[0087] The significant difference between the data from Example 2 and Comparative Example 1 lies in the long-term stability of ice adhesion. The increase in the 10th critical speed of Comparative Example 1 is much higher than that of Example 2, and the difference widens after wear resistance. This divergence is presumably directly related to the absence of vinyltrimethoxysilane. When this component is replaced by acrylamide, although the number of hydrophilic groups increases, the crosslinking network loses its siloxane bonding ability. Data characteristics indicate that vinyltrimethoxysilane may form covalent crosslinks with organosilicon prepolymers, allowing the core-shell intermediate layer to be deeply embedded in the coating bulk structure; at the same time, its hydrophobic siloxane segments may regulate the surface energy gradient, avoiding the enhanced ice core anchoring effect caused by excessive exposure of hydrophilic groups. The absence of this component leads to a continuous decay of the interfacial bonding force dominated by physical crosslinking under cyclic stress.

[0088] In Comparative Example 2, the initial ice adhesion of the coating after removing acrylamide was higher than that of Example 2, and the difference widened after wear. This phenomenon suggests that the hydrophilic amide groups of acrylamide do not only play a short-term compatibilizing role. The key mechanism may be reflected in two aspects: first, the construction of molecular-level hydrophilic regions on the core-shell surface, which binds the interfacial water molecule layer through hydrogen bonds and reduces the driving force for ice crystal epitaxial growth; second, the formation of a hydrogen bond network between the amide groups and the hydroxyl groups on the silica surface, which enhances the bonding strength of the core-shell interface. The difference in the degree of performance degradation after wear in the comparative data is particularly significant, reflecting that when this component is missing, the microstructure of the coating surface is more prone to irreversible damage under mechanical stress, resulting in the failure of the hydrophilicity regulation function.

[0089] Reversing the reaction steps led to a degradation in several properties of Comparative Example 3. Not only was the initial value of ice adhesion higher, but the degradation rate was also significantly increased after cyclic testing, and the low-temperature impact resistance level also decreased significantly. This systematic degradation indicates that the formation sequence of the core-shell structure is decisive for the spatial arrangement of the functional layers. Example 2 used a crosslinking followed by fluorination step, presumably to position the hydrophobic fluorine chains mainly in the outermost layer, while the hydrophilic crosslinking network forms a buffer phase between the fluorine layer and the silicon core. When the order is reversed (Comparative Example 3), the fluorine chains directly encapsulating the silicon core may lead to: 1) hindered crosslinking of the inner layers, resulting in insufficient network density; 2) the fluorine chains being deeply buried inside the structure, weakening the surface energy regulation effect; 3) increased phase separation, generating structural defect points, causing cracks to preferentially propagate along the core-shell interface during low-temperature impact.

[0090] Comparative Example 4, which uses only fluorine monomer modification, shows that although the initial ice adhesion is comparable to that of Example 2, the performance deteriorates sharply during cyclic testing (the value doubles in the 10th cycle), and the low-temperature impact resistance is significantly worsened. This characteristic of initial decline followed by collapse corroborates the inherent defects of single fluorine chain modification: 1) the polarity difference between the short fluorine chain and the organosilicon bulk induces phase separation, forming stress concentration channels during freeze-thaw cycles; 2) the surface energy regulation function is distributed at a single point, lacking a multi-level energy dissipation mechanism supported by a network. In contrast, the three-layer core-shell structure of Example 2 disperses mechanical stress through a cross-linked network, enabling the fluorine chain to form a continuous and stable low-energy barrier on the surface.

[0091] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

Claims

1. A long-lasting anti-icing coating containing polysiloxane, characterized in that, The product is prepared by weight from the following raw materials: 30-50 parts hydroxyl polysiloxane, 5-10 parts dimethyl silicone oil, 6-14 parts tetraethyl orthosilicate, 10-20 parts fluorine-modified crosslinkable core-shell silica, 0.5-1 part dibutyltin dilaurate, 100-200 parts tetrahydrofuran, and 30-70 parts deionized water. The preparation steps of the fluorine chain modified crosslinkable core-shell silica are as follows: S1: Vinyltrimethoxysilane graft-modified nano-silica yields alkenylated silica; S2: First, acrylamide, vinyltrimethoxysilane and N,N'-methylenebisacrylamide are crosslinked and polymerized on the surface of alkenylated silica. After crosslinking polymerization, hexafluorobutyl acrylate is further grafted and polymerized to obtain fluorine-chain modified crosslinkable core-shell silica.

2. The long-lasting anti-icing coating containing polysiloxane according to claim 1, characterized in that, The viscosity of the hydroxyl polysiloxane is 10,000-50,000 mPa·s; the viscosity of the dimethyl silicone oil is 150-250 mPa·s.

3. The long-lasting anti-icing coating containing polysiloxane according to claim 1, characterized in that, The average particle size of the nano-silica in step S1 is 20-100 nm.

4. The long-lasting anti-icing coating containing polysiloxane according to claim 1, characterized in that, In step S1, the weight ratio of vinyltrimethoxysilane to nano-silica is 0.3-0.7:8-12.

5. The long-lasting anti-icing coating containing polysiloxane according to claim 1, characterized in that, In step S2, the weight ratio of acrylamide, vinyltrimethoxysilane, N,N'-methylenebisacrylamide, alkenylated silica, and hexafluorobutyl acrylate is 5-15:3-7:0.5-1.5:8-12:10-20.

6. A method for preparing a long-lasting anti-icing coating containing polysiloxane according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Add hydroxyl polysiloxane, dimethyl silicone oil and tetraethyl orthosilicate to a mixed solvent of tetrahydrofuran and deionized water, stir at room temperature for 20-40 min, then add fluorine chain modified crosslinkable core-shell silica and dibutyltin dilaurate, continue stirring for 15-25 min, then raise the temperature to 45-55℃, continue stirring for 40-60 min to obtain a prepolymer dispersion; (2) The aluminum alloy substrate is ultrasonically cleaned, dried with nitrogen, and then plasma treated to obtain a pretreated substrate. (3) Spray the prepolymer dispersion onto the surface of the pretreated substrate, let it stand to level, cure, and then let it cool naturally to room temperature to obtain a long-lasting anti-icing coating containing polysiloxane.

7. The method for preparing a long-lasting anti-icing coating containing polysiloxane according to claim 6, characterized in that, In step (2), the plasma treatment is performed using an oxygen plasma treatment machine with a power of 80-120 W and a time of 1-3 min.

8. The method for preparing a long-lasting anti-icing coating containing polysiloxane according to claim 6, characterized in that, In step (3), the spraying pressure is 0.2-0.4 MPa and the nozzle distance is 10-20 cm.

9. The method for preparing a long-lasting anti-icing coating containing polysiloxane according to claim 6, characterized in that, In step (3), the curing process involves pre-curing at 60-70℃ for 15-25 minutes, followed by heating to 115-125℃ for 1-3 hours.

10. The method for preparing a long-lasting anti-icing coating containing polysiloxane according to claim 6, characterized in that, The thickness of the long-lasting anti-icing coating containing polysiloxane in step (3) is 15-25 μm.